Emerging Trends in Business An Interdisciplinary Approach - Baykal, Mehmet; Kazan, Halim (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2018)
This book presents a collection of interdisciplinary chapters covering the most informative issues in various fields of both theoretical and applied business. The contributors focus on up-to-date developments in business areas such as innovation, entrepreneurship, banking and digital marketing.